2016
DOI: 10.1017/s1751731115002281
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic correlations among feed efficiency, production and selected conformation traits in dairy cows

Abstract: The difficulties and costs of measuring individual feed intake in dairy cattle are the primary factors limiting the genetic study of feed intake and utilisation, and hence the potential of their subsequent industry-wide applications. However, indirect selection based on heritable, easily measurable, and genetically correlated traits, such as conformation traits, may be an alternative approach to improve feed efficiency. The aim of this study was to estimate genetic and phenotypic correlations among feed intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
24
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
11
24
3
1
Order By: Relevance
“…Veerkamp and Brotherstone (1997) observed a genetic correlation of 0.34 between DMI and body depth which is in agreement with the estimate from the current study and slightly lower than the more recent estimates (0.44 and 0.49) by Manafiazar et al (2016) and ManzanillaPech et al (2016), respectively. The genetic correlation between DMI and stature (0.34) observed in the present study was higher than reported by others (Veerkamp and Brotherstone 1997;Parke et al 1999) but comparable to the estimates reported by Manafiazar et al (2016) and Manzanilla-Pech et al (2016). Vallimont et al (2010) also observed positive genetic correlations between stature and intake traits (0.55-0.63).…”
Section: Phenotypic and Genetic Correlations' Estimatessupporting
confidence: 92%
See 3 more Smart Citations
“…Veerkamp and Brotherstone (1997) observed a genetic correlation of 0.34 between DMI and body depth which is in agreement with the estimate from the current study and slightly lower than the more recent estimates (0.44 and 0.49) by Manafiazar et al (2016) and ManzanillaPech et al (2016), respectively. The genetic correlation between DMI and stature (0.34) observed in the present study was higher than reported by others (Veerkamp and Brotherstone 1997;Parke et al 1999) but comparable to the estimates reported by Manafiazar et al (2016) and Manzanilla-Pech et al (2016). Vallimont et al (2010) also observed positive genetic correlations between stature and intake traits (0.55-0.63).…”
Section: Phenotypic and Genetic Correlations' Estimatessupporting
confidence: 92%
“…Vallimont et al (2010) also observed positive genetic correlations between stature and intake traits (0.55-0.63). Final score, which represents overall conformation score of a cow, had the lowest genetic correlation with intake traits (0.16) in the present study, which is lower than the estimate (0.25) reported by Manafiazar et al (2016). In other words, genetically taller, deeper, and more angular cows could have increased intake capacity.…”
Section: Phenotypic and Genetic Correlations' Estimatescontrasting
confidence: 86%
See 2 more Smart Citations
“…Breed was, however, a significant factor in height increase from 1 to 63 days, which was greater for Holsteins than other breeds. Holsteins have been selected for stature, which has positive genetic correlations with milk yield and feed efficiency (Lin et al, 1987;Manafiazar et al, 2016).…”
mentioning
confidence: 99%